Spark Ignition Engine Combustion, Performance and Emission Products from Hydrous Ethanol and Its Blends with Gasoline - Musaab O. El-Faroug; Fuwu Yan; Maji Luo; Richard Fiifi Turkson (Energies, 2016)
This paper reviews the serviceability of hydrous ethanol as a clean, cheap and green renewable substitute fuel for spark ignition engines and discusses the comparative chemical and physical properties of hydrous ethanol and gasoline fuels. The significant differences in the properties of hydrous ethanol and gasoline fuels are sufficient to create a significant change during the combustion phase of engine operation and consequently affect the performance of spark-ignition (SI) engines. The stability of ethanol-gasoline-water blends is also discussed. Furthermore, the effects of hydrous ethanol, and its blends with gasoline fuel on SI engine combustion characteristics, cycle-to-cycle variations, engine performance parameters, and emission characteristics have been highlighted. Higher water solubility in ethanol‑gasoline blends may be obviously useful and suitable; nevertheless, the continuous ability of water to remain soluble in the blend is significantly affected by temperature. Nearly all published engine experimental results showed a significant improvement in combustion characteristics and enhanced engine performance for the use of hydrous ethanol as fuel. Moreover, carbon monoxide and oxides of nitrogen emissions were also significantly decreased. It is also worth pointing out that unburned hydrocarbon and carbon dioxide emissions were also reduced for the use of hydrous ethanol. However, unregulated emissions such as acetaldehyde and formaldehyde were significantly increased.